Clinical surgery made easy a companion to problem-based learning - De Silva, Mohan (Tfm Pub., 2008)
Creating a differential diagnosis and rationalising a treatment plan is a challenging task for medical students and young doctors at the early stage of their training. This book also addresses the essentials; common clinical encounters, a clinical decision-making approach, care pathways, and the essential core knowledge of clinical anatomy.